Flat electrode diameter effect on glow discharge structure and properties - Lisovskiy, V.A.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2019)
This paper is devoted to studying the effect of flat electrode diameter values on current-voltage characteristics and axial structure of the glow discharge in nitrogen. We have demonstrated that the discharge current increases with the electrode diameter growing. One has to apply a considerably higher voltage across small electrodes than across large ones to transport one and the same current. The discharge structure evolves at the current fixed in such a way that a thinner cathode sheath forms near the small cathode, the negative glow length is substantially larger, and the positive column is shorter than in the case of employing large diameter electrodes. In the negative glow we have observed maxima in the axial profiles of the emission lines of nitrogen molecules and ions measured with the optical spectrometer. On moving away from the cathode, the line intensities decrease uniformly till the positive column indicating the presence of fast electrons not only in the negative glow but also in the dark Faraday space. Досліджено вплив діаметра плоских електродів на вольт-амперні характеристики і осьову структуру тліючого розряду в азоті. Показано, що розрядний струм із зростанням діаметра електродів збільшується. Для перенесення одного і того ж струму потрібно прикладати до малих електродів набагато більш високу напругу, ніж до великих. Це призводить до того, що при фіксованому струмі поблизу малого катода формується більш тонкий катодний шар, довжина негативного світіння істотно більша, а позитивний стовп коротший, ніж при використанні електродів великого діаметра. На виміряних за допомогою оптичного спектрометра осьових профілях інтенсивності ліній випромінювання молекул і іонів азоту максимуми спостерігаються в негативному світінні. При віддаленні від катода інтенсивності ліній монотонно зменшуються аж до позитивного стовпа, що вказує на наявність швидких електронів не тільки в негативному світінні, а і в темному фарадеєвому просторі. Исследовано влияние диаметра плоских электродов на вольт-амперные характеристики и осевую структуру тлеющего разряда в азоте. Показано, что разрядный ток с ростом диаметра электродов увеличивается. Для переноса одного и того же тока нужно прикладывать к малым электродам гораздо более высокое напряжение, чем к большим. Это приводит к тому, что при фиксированном токе вблизи малого катода формируется более тонкий катодный слой, длина отрицательного свечения существенно больше, а положительный столб короче, чем при использовании электродов большого диаметра. На измеренных с помощью оптического спектрометра осевых профилях интенсивности линий излучения молекул и ионов азота максимумы наблюдаются в отрицательном свечении. При удалении от катода интенсивности линий монотонно уменьшаются вплоть до положительного столба, что указывает на наличие быстрых электронов не только в отрицательном свечении, но и в темном фарадеевом пространстве.